Beyond the cultural turn : new directions in the study of society and culture - Biernacki, Richard, 1956-; Bynum, Caroline; Feierman, Steven; Halttunen, Karen, 1951-; Jacob, Margaret C.; Rose, Sonya O.; Seigel, Jerrold; Sewell, William H., Jr., 1940-; Somers, Margaret R. (Studies on the history of society and culture, 1999)
Nothing has generated more controversy in the social sciences than the turn toward culture, variously known as the linguistic turn, culturalism, or postmodernism. This book examines the impact of the cultural turn on two prominent social science disciplines, history and sociology, and proposes new directions in the theory and practice of historical research.